Removal of Anthraquinone Dye via Struvite: Equilibria, Kinetics, Thermodynamics, Fuzzy Logic Modeling - Yetilmezsoy, Kaan; Ozcimen, Didem; Kocer, Anil Tevfik; Bahramian, Majid; Kiyan, Emel; Akbin, Havva Melda; Goncaloglu, Bulent Ilhan (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
Adsorption potential of the struvite (recovered from the high-strength ammonium-rich synthetic wastewater) was explored for the first time for the removal of an anthraquinone dye (Remazol Brilliant Blue R, RBBR) from aqueous phases. According to the experimental findings obtained from the RBBR-struvite adsorption system, the maximum dye removal efficiency (approximate to 79%) was achieved at pH of 2.0, adsorbent dose of 40 g/L, initial dye concentration of 80 mg/L, contact time of 60 min, and temperature of 60 degrees C. Adsorption isotherms showed that both Langmuir and Freundlich isotherm models fitted very well to the experimental data (R-2 > 0.990), and adsorption kinetics were satisfactorily described by the Ho and McKay's PSO kinetic model (R-2 approximate to 0.990). Based on the Langmuir isotherm model, the maximum adsorption capacity of the struvite for the RBBR dye was determined as 21.73 mg/g. The sample exhibited a mesoporous structure and had a BET surface area of 16.35 m(2)/g. Thermodynamic parameters (Delta G degrees, Delta H degrees, and Delta S degrees) confirmed that the adsorption of the RBBR dye onto the struvite was spontaneous and endothermic in nature and reflected the enhanced degree of disorderliness at the solid/liquid interface, respectively. A MIMO (multiple inputs and single output) Mamdani-type fuzzy inference system was developed for the first time in modeling of the RBBR-struvite adsorption system. The proposed fuzzy logic model showed a superior prediction performance (R-2 approximate to 0.980) when compared to the conventional multiple regression methodology. Overall experimental and statistical results confirmed that struvite could be used as a promising adsorbent material for anthraquinone dye removal from aqueous solutions.
Keywords: Adsorption; Remazol brilliant blue R; Struvite; Dye removal; Modeling; Fuzzy logic; REMAZOL BRILLIANT BLUE; MESOPOROUS ACTIVATED CARBON; WASTE-WATER; AQUEOUS-SOLUTION; METHYLENE-BLUE; ADSORPTION BEHAVIOR; ANIONIC DYES; ORANGE PEEL; TEXTILE DYE; OPTIMIZATION; Environmental Sciences & Ecology